The effect of plyometric exercises with a proposed device on the development of reaction speed and defensive movement in basketball players under the age of 18 - Abdel Abbas , Ali; Abdel Hussein , Huda (Journal of Physical Education, 2025)
The study aimed to develop plyometric exercises with a proposed device to enhance reaction speed and defensive movement in basketball players under the age of 18. The researchers used an experimental approach, employing an equivalent control-experimental group design and conducting pre- and post-tests. The research sample was selected from Al-Nu’maniya Sports Club’s youth category (under 18 years old). The results of the pre- and post-tests were presented, analyzed, and discussed using data processing methods. The researchers concluded that plyometric exercises with the proposed device had a positive impact on enhancing reaction speed and defensive movement in players under 18 years old. They also recommended several actions, including the necessity of using plyometric exercises designed by the researchers to enhance reaction speed and defensive movement in young players. Moreover, they emphasized the importance of utilizing modern training devices to develop physical fitness attributes and defensive skills in basketball players under 18 years old.